Identification of collapsin response mediator protein-2 as a potential marker of colorectal carcinoma by comparative analysis of cancer cell secretomes - Wu, Chih-Ching; Chen, Hua-Chien; Chen, Su-Jen; Liu, Hao-Ping; Hsieh, Yi-Yueh; Yu, Chia-Jung; Tang, Reiping; Hsieh, Ling-Ling; Yu, Jau-Song; Chang, Yu-Sun (Proteomics (Weinheim), 2008)
The cancer cell secretome may contain many potentially useful biomarkers. We therefore sought to identify proteins in the conditioned media of colorectal carcinoma (CRC) cell lines but not in those from other cancer cell lines. The secretomes of 21 cancer cell lines derived from 12 cancer types were analyzed by SDS-PAGE combined with MALDI-TOF MS. Among the 325 proteins identified, collapsin response mediator protein-2 (CRMP-2) was chosen for evaluation as a potential CRC biomarker, since it was selectively detected in the CRC cell line secretome and has never been reported as a cancer biomarker. Immunohistochemical analysis of 169 CRC specimens showed that CRMP-2 was positively detected in 58.6% of the tumors, but weakly or not detected in >90% of the adjacent nontumor epithelial cells. Moreover, the CRMP-2-positive rate was significantly increased in earlier stage tumors and lymph node metastasis. Plasma CRMP-2 levels were significantly higher in CRC patients (N = 201) versus healthy controls (N = 201) (61.3 ± 34.6 vs. 40.2 ± 24.3 ng/mL, p = 0.001). Our results indicate that comparative analysis of cancer cell secretome is a feasible strategy for identifying potential cancer biomarkers, and that CRMP-2 may be a novel CRC biomarker.